A practical guide to reporting appraisal and transparency in qualitative research in health professions education - Lin, Galvin Sim Siang; Foong, Chan Choong; Mohd Noor, Mohamad Nabil; Cabatan, Maria Concepcion (Springer Nature, 2026)
Qualitative research plays an increasingly important role in health professions education by exploring the meaning, process, and context that cannot be captured through quantitative approaches alone. It allows researchers to understand how patients, students, and practitioners experience, interpret, and act within clinical and educational environments, offering insights that are essential for improving curricula, practice, and policy. Despite its value, qualitative research has often been criticised for lacking transparency and rigour, particularly in areas such as sampling, analytic procedures, and researcher reflexivity. To address these concerns, structured reporting standards, such as the Consolidated Criteria for Reporting Qualitative Research (COREQ) and Standards for Reporting Qualitative Research (SRQR), were developed to enhance clarity, reproducibility, and appraisal. A range of appraisal tools is also available, with the Critical Appraisal Skills Programme (CASP) and the Joanna Briggs Institute (JBI) checklist widely used in health professions research, alongside other newer approaches such as the Differentiated Qualitative Appraisal (DiQuAl) tool. This review provides an overview and practical guide to reporting, appraisal, and transparency in qualitative research within health professions education. It discusses the evolution of reporting standards, compares key frameworks, highlights the importance of reflexivity and trustworthiness, and outlines practical strategies for embedding reporting guidelines throughout the research process. By integrating these approaches, researchers can produce more credible, transferable, and impactful qualitative scholarship.